Terrorism and political contention: new perspectives on North Africa and the Sahel region - Besenyő, János; Issaev, Leonid; Korotaev, Andrej Vitalʹevič (Perspectives on Development in the Middle East and North Africa (MENA) Region, 2024)
Chapter 1. Introduction: Terrorism and Political Contention in North Africa and the Sahel Region (János Besenyő) -- Part I. Terrorism and Political Contention in North Africa and the Sahel Region: Factors, Patterns, Regularities -- Chapter 2. Migration and Terrorism in North Africa (Viktor Glied) -- Chapter 3. Terrorist Financing from North Africa to the Sahel Region: Exhaustible or Inexhaustible Stream? (Szabolcs Pásztor) -- Chapter 4. Female Vulnerabilities for Terrorist Activities in North Africa and the Sahel Zone (Nina Käsehage) -- Chapter 5. “Chasse Gardée” or “Faubourg”?: Politico-Military Interventions of France in the Sahel Region (András István Türke) -- Chapter 6. The Ukrainian Conflict's Impact on the Prevailing Causes for Radicalization in North Africa (János Besenyő) -- Chapter 7. Coupvolution as a Mechanism of Regime Change in the Sahel (Egor Fain) -- Part II. Country Particularities of Terrorism and Political Contention in the Region.